(untitled) (Research, Society and Development, 2019)
In this article, the objective is to verify the qualitative analyzes in an educomunicative perspective of infographic genres of Revista Superinteressante in activity carried out with elementary school students of a public school of São Sepé in the scope of the construction of collective and emotional intelligence. For this investigation, were used as fundamentals Soares (2011), Aparici (2014), Teixeira (2015), Paiva (2011), Abrahão (2012), among others. The methodological procedures involved the selection of the corpus, the definition of infographics for practice and analysis, and the organization of research criteria and analysis procedures. This proposal required a description of the activities. The infographics applied in the classroom demonstrate the multimodal nature of the mediatic text and the construction of interrelated meanings through verbal and nonverbal languages.